S92 Calcium-sensing receptor as a therapeutic target for pulmonary fibrosis. (12th November 2019) - Wolffs, K; Mansfield, B; Bruce, R; Verckist, L; Paes De Araújo, R; Attanoos, R; Ward, J; Corrigan, C; Kemp, P; Adriaensen, D; Mur, L; Hope-Gill, B; et al.
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a disease with very poor prognosis and no curative therapies. The extracellular calcium-sensing receptor (CaSR) is a chemosensor which is activated by several agonists/modulators including polyvalent cations, polyamines, and basic polypeptides. Previously we and others have shown that CaSR activation drives pulmonary inflammation and remodelling in preclinical models of asthma, COPD and pulmonary hypertension. The aims of the study are to investigate the role of the CaSR in pulmonary fibrosis and evaluate the scientific rationale for repurposing CaSR antagonists (calcilytics) as potential novel therapeutics for IPF. Methods: Immunostaining was used to assess lung CaSR expression in IPF patients and control. CaSR-related metabolites were assessed in patient saliva samples (IPF and control) using high-resolution mass spectrometry. In primary human lung fibroblasts (HLF), the polyamine, spermine, was used to assess the functional activation of the CaSR via calcium imaging. HLF were also treated with transforming growth factor-β1 (TGF-β1) in the presence or absence of calcilytics to assess expression of known fibrotic markers and CaSR. Histology was carried out in 15 month old mice with targeted CaSR deletion from sm22α-positive cells to assess age-induced lung remodelling. Results: CaSR expression was increased in specific cells of the IPF lungs compared to controls. The expression of several CaSR activators (amines and polyamines) was significantly increased in IPF patients compared to control (p<0.05). In human lung fibroblasts, calcilytics prevented spermine-induced increase in intracellular calcium concentration. Calcilytics also suppressed the effects of exogenous TGF-β1 supplementation on α-smooth muscle actin expression, proliferation, collagen deposition, and inflammation (p<0.01). Selective CaSR deletion from fibroblasts and smooth muscle cells protected mice from age-induced fibrosis (p<0.05). Conclusions: This study supports the role of the CaSR in PF, as receptor deletion significantly attenuates fibrosis. Since CaSR activators are elevated in IPF patient saliva, increased levels of these metabolites suggest a role for the CaSR in the pathophysiology of IPF. The efficacy of calcilytics in reducing pro-fibrotic changes seen in activated lung fibroblasts further supports the development of calcilytics as a novel treatment for IPF.